Gravitational Field Concepts and Applications - Essa, Khalid S. (IntechOpen, 2022)
This book presents a comprehensive overview of gravity and gravitational fields. The eight chapters are presented in two sections. Chapters in the first section address such topics as the theory of gravity, transient gravitational forces, the nature of our temporal universe, and photo-gravitational celestial mechanics. Chapters in the second section discuss how to create a gravity survey, analyze data collected by satellites and on the ground, and present visualizations of several field cases around the world.